Model Simulasi Pangan Di Pusat Distribusi Provinsi Banten Dengan Pendekatan Sistem Dinamis - Heru Winarno; Syaina Ulfah Azhara; Syahrul M Dhani (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The development of food commodities in Banten province, with geographical conditions where the area is mostly agricultural and with a fairly large population, has an important role, one of which is as a food buffer on the island of Java. Many harvests are distributed directly outside the region, after which they enter the market through distributors and agents, so this is a point of weakness and deficiency for policy makers in regulating and distributing rice commodities. This research was conducted with the aim of knowing the rice distribution model using the Powersim application. The method used to create a food policy model/design for Banten province is the Dynamic System. The results of this research are that the output obtained from the rice food distribution model simulation is that each rice stock in the Gapoktan warehouse sends according to the amount requested in each district/city, with a total capacity that can be obtained at the food distribution center of 109,682 tonnes/yr, or 2,742 tons/harvest. Then, after carrying out a simulation model using Powersim software, it can be concluded that the rice food commodity in Banten Province can still meet demand. With the Banten Province Food Distribution Center, it can control the availability of rice.